Why European banks adjust their dividend payouts? - Marco Belloni; Maciej Grodzicki; Mariusz Jarmuzek (European Central Bank (ECB), 2023)
Economic literature suggests that banks change their dividend payouts for three main reasons. They may be willing to signal good future profitability to shareholders to address information asymmetry, or use dividends to mitigate the agency costs, or could come under pressure from prudential supervisors and regulators to retain earnings. The COVID-19 pandemic led to introduction of sector-wide recommendation by regulators to suspend dividend payouts in view of prevailing large uncertainty. Using a panel data approach for two samples of listed and unlisted European banks, this paper provides evidence that, over a decade and a half preceding the pandemic, bank dividend payouts were adjusted in line with the three motivations found in the literature. The results are robust to selection of alternative variables representing these motivations. Banks are found not to discount expectations about future economic conditions or their own profitability when making payouts. Simulations shown in the paper suggest that, in the absence of supervisory recommendations, banks would likely have reduced the payouts only slightly in the first year of the pandemic.
Keywords: G21; G35; 330; bank dividends; payout policies; financial regulation